Merawat Bumi sebagai Tanggung Jawab Iman - Edi Purwanto (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
Global environmental crises demand new approaches to conservation, including religious perspectives such as Christianity. The Christian perspective provides a significant theological and ethical framework for environmental management. This study aims to explore and analyze the contribution of the Christian perspective to environmental management through a systematic literature review approach. This study employs a systematic literature review approach to explore ecological concepts within Christianity. Data were collected from major academic databases such as Scopus and Google Scholar, focusing on eco-theology and environmental management from a Christian viewpoint. Findings indicate that Christian doctrines of creation and stewardship support environmental responsibility. Interfaith dialogue, integrating Christian spirituality with ecological issues, and a comprehensive eco-theological understanding are crucial for addressing environmental crises. This research encourages the Christian community to actively engage in environmental conservation efforts and develop management strategies grounded in spiritual values. Dialogue and collaboration among religious communities can enhance global sustainability efforts.